Incorporation of zirconium in medium-pore aluminophosphate molecular sieves with AEL framework - Ganguli, J. N.; Chakrabortty, Dhruba; Satyanarayana, C. V. V. (Microporous and Mesoporous Materials, 2008)
Zirconium incorporated alurninophosphate molecular sieves ZrAPO-11 was synthesized by hydrothermal method. The samples were characterized by X-ray diffraction (XRD), scanning electron microscopy, thermogravimetric/differential thermal analysis (TGA/DTA), diffuse reflectance UV-visible spectroscopy, magic-angle spinning nuclear magnetic resonance (MAS NMR) spectroscopy (P-31 and Al-27). The acidity of the materials were determined by temperature programmed desorption (TPD) of ammonia. X-ray diffraction and scanning electron microscopy reveals formation of crystalline material in pure phase. Thermal analysis shows higher template content in zirconium containing samples than the corresponding AlPOs. MAS NMR suggests incorporation of zirconium in the framework. TPD reveals that the ZrAPO-11 samples were of higher acidity than AIPO(4)-11 (c) 2007 Elsevier Inc. All rights reserved.
Keywords: AlPO4-11; Aluminophosphate; catalysis; Molecular sieve; ZrAPO-11